2023
DOI: 10.1162/netn_a_00271
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of the spatial distributions between sMRI and PET reveals the progression of Alzheimer’s disease

Abstract: Introduction: Amyloid-beta (Aβ) deposition and altered brain structure are the most relevant neuroimaging biomarkers for Alzheimer’s disease (AD). However, their spatial inconsistency was always confusing and misleading. Furthermore, the relationship between this spatial inconsistency and AD progression is unclear. Methods: The current study introduced a regional radiomics similarity network (R2SN) to map structural MRI and Aβ positron emission tomography (PET) images to study their cross-modal interregional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…This integration, in turn, offers a novel insight into AD mechanisms from a connectome perspective. Our recent studies have demonstrated that R2SN can accurately capture the structural connectome changes in AD (Zhao et al, 2023; Zhao et al, 2021; Zhao et al, 2022). Additionally, our findings show a correlation between RMCS and cognitive ability and microstructural genetics, further emphasizing the significance of investigating brain connectome changes in other disorders using R2SN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This integration, in turn, offers a novel insight into AD mechanisms from a connectome perspective. Our recent studies have demonstrated that R2SN can accurately capture the structural connectome changes in AD (Zhao et al, 2023; Zhao et al, 2021; Zhao et al, 2022). Additionally, our findings show a correlation between RMCS and cognitive ability and microstructural genetics, further emphasizing the significance of investigating brain connectome changes in other disorders using R2SN.…”
Section: Discussionmentioning
confidence: 99%
“…The employment of interregional similarity networks, particularly in the context of structural covariance networks (SCNs), has demonstrated the capacity to capture synergistic alterations in morphological architecture across distinct brain regions (Bethlehem et al, 2017; Binnewijzend et al, 2014; Dai et al, 2019; Kim et al, 2016; Li et al, 2021; Yao et al, 2010; Yu et al, 2018; Zheng et al, 2015). Furthermore, SCNs have exhibited efficacy in investigating the dysfunction of the connectome within the spectrum of AD, thereby yielding a comprehensive array of anatomical indices that serve to discriminate AD and demarcate subtypes of MCI patients (Fu et al, 2021; Montembeault, Rouleau, Provost, Brambati, & Alzheimer's Disease Neuroimaging, 2016; Tijms et al, 2012; Yu et al, 2018; Zhao et al, 2021; Zhao et al, 2022; Zhao et al, 2023). While the SCN has garnered diverse applications in the context of AD, how the connectome changes in AD and what is related to those variations are not well‐established.…”
Section: Introductionmentioning
confidence: 99%
“…One interesting use of traditional radiomics measures has been their integration into studies of structural connectivity networks. A series of papers published by Zhao and colleagues have introduced regional radiomics similarity networks and utilized them to characterize connectome changes, 17 , 33 , 34 relate them to progression of cognitive decline, 35 and even to gene expression patterns. 33 A similar approach was proposed by Liu et al who constructed structural similarity networks based on radiomics measures.…”
Section: Use Of Traditional Radiomics In Adrd Neuroimagingmentioning
confidence: 99%